Pengaruh Kepemilikan Institusional, Kepemilikan Manajerial, dan Kepemilikan Asing Pada Pengungkapan Corporate Social Responsibility - Adiputri Singal, Patrisia; Wijana Asmara Putra, I Nym (E-Jurnal Akuntansi; Vol 29 No 1 (2019)DO - 10.24843/EJA.2019.v29.i01.p30, 2019)
One of the factors of corporate governance that influence the implementation of CSR is the ownership structure. The emergence of corporate ownership structures results from a comparison of the number of shareholders in the company. The purpose of this study was to determine the effect of institutional ownership, managerial ownership, and foreign ownership on disclosure of corporate social responsibility (CSR). This research was conducted on the Indonesia Stock Exchange in the period 2013-2017. The sample of this research was 40 Infrastructure, Utilities and Transportation companies using purposive random sampling, where samples were taken based on certain criteria. Data collection of this study uses secondary data. The analysis technique used is the Analysis of Multiple Linear Regression. The results of this study indicate that institutional ownership and managerial ownership have a positive effect on CSR, while foreign ownership has no significant negative effect on disclosure of CSR. Keywords : Institutional Ownership; Managerial Ownership; Foreign Ownership; Disclosure Of Corporate Social Responsibility.